Embracing Islamic values through metaphorical exploration. Village of virtues: quest for light / Norasyikin Abdul Malik ... [et al.] - Abdul Malik, Norasyikin; Ya Shak, Mohamad Syafiq; Kasmaruddin, Nurhidha Irawaty; Hasni, Nurul Ain; Mohamad, Faizah (2023)
Teaching complex Islamic concepts in a virtual environment often lacks depth and resonance. Addressing this challenge, we present "Village of Virtues: Quest for Light," a transformative Roblox game that employs powerful metaphors to guide players through a virtual exploration of Islamic values. The game cleverly uses light and darkness to depict good deeds and sinful behaviour, while a resilient tree with deep roots that symbolises a high level of taqwa. Thunderstorms represent life's internal struggles, while obstacles in the journey represent devil's temptations in life. By merging metaphors with interactive gameplay, "Village of Virtues: Quest for Light" fosters a deep understanding and emotional connection. This gamification approach spotlights the game's potential to revolutionise education, specifically in teaching complex ideas or abstract concepts, bridging metaphor usage with immersive experiences.